2012
DOI: 10.1186/1556-276x-7-602
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, oxidative stress, and genotoxicity in human hepatocyte and embryonic kidney cells exposed to ZnO nanoparticles

Abstract: Traces of zinc oxide nanoparticles (ZnO NPs) used may be found in the liver and kidney. The aim of this study is to determine the optimal viability assay for using with ZnO NPs and to assess their toxicity to human hepatocyte (L02) and human embryonic kidney (HEK293) cells. Cellular morphology, mitochondrial function (MTT assay), and oxidative stress markers (malondialdehyde, glutathione (GSH) and superoxide dismutase (SOD)) were assessed under control and exposed to ZnO NPs conditions for 24 h. The results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(97 citation statements)
references
References 28 publications
8
87
0
2
Order By: Relevance
“…When HEK 293 cell line was treated with 0-100 μg/mL zinc oxide nanoparticles for 24 h, it was observed that there was a reduction in cell viability. Results also demonstrated DNA damage, oxidative stress and mitochondrial damage [218]. Similarly, when human bronchial epithelial cells were treated with zinc oxide at 100 μg/mL, the observed effects include the release of LDH, decrease in cell viability and oxidative stress [219].…”
Section: Mechanistic Studiesmentioning
confidence: 92%
“…When HEK 293 cell line was treated with 0-100 μg/mL zinc oxide nanoparticles for 24 h, it was observed that there was a reduction in cell viability. Results also demonstrated DNA damage, oxidative stress and mitochondrial damage [218]. Similarly, when human bronchial epithelial cells were treated with zinc oxide at 100 μg/mL, the observed effects include the release of LDH, decrease in cell viability and oxidative stress [219].…”
Section: Mechanistic Studiesmentioning
confidence: 92%
“…12 Other, more recent reports demonstrate the use of these cells for investigating the potential toxicity of nanoparticles. [13][14][15][16] Andelman et al examined the effects of exposure to different types of Y 2 O 3 NPs on human foreskin fibroblast cells and demonstrated a concentration-dependent (25-500 µg/mL) cytotoxicity by live/dead cell assay. 10 To investigate the potential mechanisms of the Y 2 O 3 NPs toxicity, we exposed the HEK293 cells to different concentrations of NPs to first determine the acute cytotoxic dose (IC 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…For formation of curcumin loaded chitosan nanoparticles, varied concentrations of curcumin were added in the organic phase along with lecithin. Alginate coated lecithin/chitosan nanoparticles (ALG-LCN) were prepared by the slight modifications in the met hod described by Bagre et al and Lie et al [18][19] Briefly 10 mg/ml concentration sodium alginate stock solution was prepared. The curcumin loaded and blank lecithin/ chitosan nanoparticles after preparation were subjected to ultracentrifugation at 5000 rpm speed (REMI, India) for 4 h. The centrifugation at this controlled speed allowed formation of LCN concentrated suspension layer near bottom of centrifuge tubes and clearer solution at the top.…”
Section: Preparation Of Loaded and Unloaded Lecithin/ Chitosan Nanopamentioning
confidence: 99%